Implementasi Konsep Eksistensi, Inovasi, Regenerasi pada Interior Pusat Komunitas Ludruk Irama Budaya Sinar Nusantara di Surabaya - Immaculata, Immaculata; Wardani, Laksmi Kusuma; Frans, Stephanie Melinda (Intra, 2018)
Ludruk as a traditional performing art of East Java is often considered as an old, abandoned culture in Surabaya. However, there is one of ludruk group that still survives, named Ludruk Irama Budaya Sinar Nusantara Community. In order to preserve ludruk, this community performs every week and trains youngster. In order to achieve this purpose, this community needs a platform to maintain ludruk as Surabaya’s authentic performing art. The theme is inspired by the spirit of the community to preserve ludruk to its vision and mission which is existence, innovation, and regeneration. This concept of existence is applied to centralized organization of spaces, homey atmosphere, naturalism character, and self-service system. The concept of innovation is applied to the use of technology and multifunctional space. Meanwhile, the concept of regeneration is applied to an open space and easy access for everyone. With this design, the existence, innovative, and regenerative ambience is brought to live by everyone who enters the platform.